OPTIMALISASI SUMBER DAYA ALAM MELALUI PENINGKATANPRODUKTIVITAS KRIPIK EMPING DAN SELAI PISANG SEBAGAI PRODUK UNGGULAN DESA PERDANA KECAMATAN SUKARESMI - Romli, Ombi; Hafizh, Gibran; Puspita, Aninda Eka (Yayasan Education and Social Center, 2025)
Perdana Village, Sukaresmi District, has the potential of natural resources that are still not maximized, especially in the processing of local agricultural and soybean products. This program aims to optimize the potential of the village through increasing the productivity of emping chips (chips from melinjo fruit) and banana jam, which are local superior products. The methods used include production technical training approaches, strengthening the capacity of micro businesses, and marketing assistance, both offline and digital. The process began with an initial survey to identify the constraints and needs of producers, followed by training on making quality banana chips and jam, improving packaging quality, and digital marketing strategies—referring to similar best practices from similar service journals. The results showed: Productivity increased significantly, with a 30–50% increase in daily output compared to before the intervention. The quality of packaging and branding are stronger so that it attracts the attention of local and digital markets. Sales are increasing, both via direct sales (stalls & village markets) and online/local platforms. Business actors gain new skills in production management and marketing, supporting the sustainability of micro businesses in villages. In conclusion, the optimization of the natural resources of Perdana Village through increasing the productivity of emping chips and banana jam is able to improve the welfare of the village community by strengthening the added value of local products so that the local products have a high selling value and are able to increase the welfare of the community, especially in Pandeglang Regency.